2012
DOI: 10.4103/0019-5049.96303
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of pressor response and dose sparing of opioids and anaesthetics with pre-operative dexmedetomidine

Abstract: Background and Aims:Alpha-2 agonists are being increasingly used as adjuncts in general anaesthesia, and the present study was carried out to investigate the ability of intravenous dexmedetomidine in decreasing the dose of opioids and anaesthetics for attenuation of haemodynamic responses during laryngoscopy and tracheal intubation.Methods:One hundred patients scheduled for elective general surgery were randomized into two groups: D and F (n=50 in each group). Group D were administered 1 μg/kg each of dexmedet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
98
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 29 publications
18
98
1
Order By: Relevance
“…The α 2 adrenoceptors have an effect on the spinal cord, especially α 2 A and α 2 C as well as modulating the descending noradrenergic pathways leading to 30% to 50% reduction in the requirements of opioids. Our study is in accordance with other studies [9,10].…”
Section: Discussionsupporting
confidence: 83%
“…The α 2 adrenoceptors have an effect on the spinal cord, especially α 2 A and α 2 C as well as modulating the descending noradrenergic pathways leading to 30% to 50% reduction in the requirements of opioids. Our study is in accordance with other studies [9,10].…”
Section: Discussionsupporting
confidence: 83%
“…The level of reduction in the required analgesic dosage was similar to that in a previous study, which suggested that a one-time injection of DEX reduced the amount of postoperative analgesics required by 50% [25]. …”
supporting
confidence: 72%
“…Similar result was seen in the Srivastava VK and Reddy SV et al 12,13 Similar result about dexmedetomidine to control HR and blood pressure after laryngoscopy observed in Lee JH et al, Bajwa SS et al and Efe EM et al study. [14][15][16] Keniya VM et al study observed that bradycardia occurred in two patients in dexmedetomidine group intraoperatively. 17 Decrease in HR was observed in our study in permissible limit but none of our patients required treatment with atropine.…”
mentioning
confidence: 99%